VICTIMOLOGICAL ASPECTS OF ETHNOPOLITICAL CONFLICT (ON THE EXAMPLE OF THE CIRCASSIAN AND CRIMEAN TATAR ETHNIC COMMUNITIES) (Revista Inclusiones, 2020)
Based on the methodology of phenomenological constructivism, constructivist structuralism, and the coherent approach to the study of ethnic identity, the present article examines the manifestations of victimhood in the formation and development of ethnopolitical conflict. The main approaches to the definition of victimhood in the designated problem area are differentiated. The first understanding of victimhood is based on a person’s ability to become a victim of a crime and the second understanding is formulated from the point of manifestation of outwardly directed deviant behavior in victims. The key contexts of manifestation of the victimological factor in ethnopolitical conflicts found in different planes of determination of this phenomenon are identified. It is established that the characteristics of the social environment in which ethnic communities function comprise victimological content. Said characteristics directly affect victimogenesis in ethnic subjects. Models of ethnic stratification and objective and subjective indicators and perceptions of ethnic status play a major role in this process. The victimological aspect can manifest in the context of the subjects’ vulnerability (at the individual and group level) against crimes and offenses committed against them based on ethnic hostility. The ethnic component acts as an indicator of the identity of a person or a group based on which a delict is committed against them.